A refractory human T-cell leukemia virus type 1-associated myelopathy/tropical spastic paraparesis patient with lymphoma-type adult T-cell leukemia/lymphoma: A case report and review of the literature. Issue 40 (8th October 2021) - Tamaki, Keiko; Mera, Hidekazu; Takeshita, Sho; Fujioka, Shinsuke; Goto, Maki; Matsumoto, Taichi; Yamano, Yoshihisa; Takamatsu, Yasushi; Tsuboi, Yoshio
Abstract: Rationale: Adult T-cell leukemia/lymphoma (ATL) and human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) are caused by HTLV-1, but the coexistence of both disorders is rare. The estimated incidence is approximately 3%. Patient concerns: A 54-year-old man was unable to stand up because of spastic paraparesis 1 month after the onset. He developed lymphadenopathy in the left supraclavicular fossa 5 months after the onset. The spastic paraplegia and sensory symptoms below the thoracic spinal cord level worsened. Diagnoses: Both blood and cerebrospinal fluid (CSF) tests were positive for anti-HTLV-1 antibodies. The patient was diagnosed with rapidly progressive HAM/TSP. He was also diagnosed with lymphoma-type ATL by the biopsy specimen of the lymph node. CSF examination at the time of symptom exacerbation showed abnormal lymphocytes, suggesting central infiltration of the ATL in the central nervous system. Interventions: Methylprednisolone pulse therapy and oral prednisolone maintenance therapy were administered for rapidly progressive HAM/TSP. Intrathecal injection of methotrexate was administered for the suggested central infiltration of the ATL. Outcomes: Methylprednisolone pulse therapy and intrathecal injection of methotrexate did not improve the patient's exacerbated symptoms. Five months later, clumsiness and mild muscle weakness of the fingers appeared, and magnetic resonance imaging showed swelling of the cervical spinal cord. Clonality analysis showed monoclonal proliferation only in the DNA of a lymph node lesion, but not in the CSF and peripheral blood cells. Lessons: This was a case of rapidly progressive HAM/TSP associated with lymphoma-type ATL that was refractory to steroids and chemotherapy. The pathogenesis was presumed to involve ATL cells in the brain and spinal cord because of the presence of abnormal lymphocytes in the CSF, but DNA analysis could not prove direct invasion. This case suggests that when we encounter cases with refractory HAM/TSP, it should be needed to suspect the presence of ATL in the background.